Pengaruh Gaya Komunikasi Guru terhadap Tingkat Keaktifan Siswa di SMP Darul Furqon - Sekar Aulia Zahara; Agustina Multi Purnomo; Sukarelawati Sukarelawati (Pusat Riset dan Inovasi Nasional, 2026)
This research focused on examining the ways teachers communicate, the engagement level of students in learning, and how teachers’ communication methods affect students’ engagement at SMP Darul Furqon. A quantitative methodology was utilized, following a causal associative research framework. The study’s population included 50 students, all of whom were chosen as the sample using a total sampling method. To gather data, a Likert-scale questionnaire that met the required standards for validity and reliability was used. The analysis of the data involved descriptive statistics, simple linear regression, t-tests, and calculating the coefficient of determination (R²). Results indicated that teachers’ communication methods were rated as very good, with an average score of 4. 40, while the learning engagement of students was rated as good, with an average score of 4. 15. The findings demonstrated that the communication styles of teachers had a significant and positive impact on students’ engagement in learning, as reflected by a significance level below 0. 001. Additionally, the coefficient of determination (R²) at 0. 505 revealed that 50. 5% of students’ learning engagement was attributed to teachers’ communication styles, with the other 49. 5% being influenced by factors not included in this research. These results suggest that employing open, clear, and interactive communication methods by teachers is crucial for improving students’ engagement in the learning process.